2013
DOI: 10.1177/0885328213510056
|View full text |Cite
|
Sign up to set email alerts
|

Human mesenchymal stem cells response to multi-doped silicon-strontium calcium phosphate coatings

Abstract: The search for apatitic calcium phosphate coatings to improve implants osteointegration is, nowadays, preferentially focused in the obtaining of compositions closer to that of the inorganic phase of bone. Silicon and strontium are both present in trace concentrations in natural bone and have been demonstrated, by separate, to significantly improve osteoblastic response on calcium phosphate bioceramics. This work aims the controlled and simultaneous multi-doping of carbonated calcium phosphate coatings with bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Recently, it was demonstrated that silicon-and silver-containing CHA provide enhanced bioactivity and antibacterial properties over pure CHA, respectively [50,51]. Besides, silicon significantly improve osteoblastic response on calcium phosphate bioceramics, probably, since it presents in trace concentrations in natural bone [52]. Therefore, this paper focuses on the synthesis of CHA coatings on silicon substrate by sol-gel processing route using spin-coating technique.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was demonstrated that silicon-and silver-containing CHA provide enhanced bioactivity and antibacterial properties over pure CHA, respectively [50,51]. Besides, silicon significantly improve osteoblastic response on calcium phosphate bioceramics, probably, since it presents in trace concentrations in natural bone [52]. Therefore, this paper focuses on the synthesis of CHA coatings on silicon substrate by sol-gel processing route using spin-coating technique.…”
Section: Introductionmentioning
confidence: 99%
“…This finding was also demonstrated by Tokudome et al who evaluated the ability of well-characterized Mg/Zn/F-CaP particles to prevent bone mineral deficiency, with results indicating that the compounds were effective in preventing bone loss and having potential use for treating osteoporosis [35]. A complete physicochemical characterization has also been performed on Si/Sr codoped CaP coatings and a significantly positive effect on the osteogenic differentiation of cells was observed, confirming the enormous potential of the approach of such coatings [36]. …”
Section: Discussionmentioning
confidence: 99%
“…They demonstrated the obtainment of dense and uniform films with a surface of nanorods (diameters between 30 and 50 nm), characterised by enhanced HAp dissolution resistance, due to the fluorine incorporation and to the nanosized structure, and improved bonding strength. Furthermore, silicate ions were co‐substituted within HAp coatings with Mn 2+ , Sr 2+ , Mg 2+ . In details, Büyükaksoy et al fabricated Mn/Si co‐substituted hydroxyapatite thin films by dip coating method.…”
Section: Bi‐substituted Hydroxyapatite Coatingsmentioning
confidence: 99%
“…Probably, the vicarios ions incorporation could induce the generation of point defects, with consequent alteration of HAp electrical properties, as testified by the blue colour of the doped samples calcined at 600−800°C and white colour afer the treatment at 1000°C . Rodríguez‐Valencia et al studied the properties of Si/Sr co‐doped HAp coatings, obtained by pulsed laser deposition (PLD) using a constant amount of Si (ie 2.5 at%) and varying the Sr amount between 0 up to 10 at%. They concluded that the increment in the concentration of one of the dopants might affect the content of the other substitutions in the coating: for example, increasing Sr leads to alterations in carbonate bands intensity and to decrement in the Ca content, in comparison to undoped HAp …”
Section: Bi‐substituted Hydroxyapatite Coatingsmentioning
confidence: 99%
See 1 more Smart Citation